COVID-19 associated aspergillosis, candidiasis, cryptococcosis, and mucormycosis infections in patients with diabetes mellitus: A systematic review - Li, Denise Vina Tan (Animo Repository, 2023)
The COVID-19 pandemic has greatly impacted the world, more so the field of healthcare. The effects of the COVID-19 virus on an individual has yet to be fully discovered and the recent rise in cases of COVID-19 associated fungal infections of aspergillosis, candidiasis, cryptococcosis, and mucormycosis is greatly concerning. The negative effects brought about by the COVID-19 infection, alongside other comorbidities like diabetes mellitus, makes patients more vulnerable to these COVID-19 associated fungal infections. The aim of this systematic review was to determine the presence of the COVID-19 associated fungal infections of aspergillosis, candidiasis, cryptococcosis, and mucormycosis in patients with diabetes mellitus and to investigate the different factors that could affect the contraction of these infections. Data for this study were collated through an online search for scholarly studies related to COVID-19 associated fungal infections with diabetes mellitus in PubMed, Scopus, and Wiley Online Library. After utilizing the inclusion and exclusion criteria, 76 studies were considered, with 96 cases as the final data. The results from the systematic study are as follows: India, with 42 out of the 96 cases (42.7%), is the country with the most cases present. The age range of 50-59 years old, garnering 30 out of the 96 cases (31.3%), is the most vulnerable age group. Males, comprising 69 out of the 96 cases (71.9%) is the more vulnerable gender. Patients with active COVID-19, comprising 51 out of the 96 cases (53.1%), are more vulnerable. The occurrence of the infections are equally found in patients with diabetes, whether they have it controlled with maintenance medicine, or have left it uncontrolled with no regular medication. Mucormycosis is the most common COVID-19 associated fungal infection comprising 65 out of the 96 cases (67.6%). Lastly, the clinical outcome for 53 out of the 96 cases (55.2%) have recovered. Obtaining these COVID-19 associated fungal infections is detrimental to one’s health, and possibly even fatal, most especially to those immunocompromised; however, an early diagnosis is essential for a complete recovery to occur. For future studies, it is recommended to look into more factors that contribute to the contraction of these COVID-19 associated fungal infections, as well as add more types of COVID-19 associated fungal infections, if any.